2021
DOI: 10.1159/000512399
|View full text |Cite
|
Sign up to set email alerts
|

Large Fundic Gland Polyp Associated with Long-Term Proton Pump Inhibitor Administration Mimicking Gastric-Type Neoplasm

Abstract: A 57-year-old man with a 10-year history of proton pump inhibitor (PPI) use presented with multiple fundic gland polyps (FGPs) including one >20 mm, whitish, semi-pedunculated polyp. Black spots and cobblestone-like mucosa were also observed in the stomach upon endoscopy; therefore, the lesion was considered to result from long-term PPI administration. Endoscopically, we diagnosed this polyp as a neoplastic lesion with gastric phenotype rather than a non-neoplastic lesion. Biopsy revealed an atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Therefore, our case was considered sporadic and probably PPI-related. A report from Japan stated that after rabeprazole was used for 104 weeks, 13.6% of patients developed new fundic gland polyps, predominantly in the gastric corpus, with sizes less than 5 mm [ 8 ]. In this index case, though there were multiple polyps in the fundus and body, a large antral polyp measuring 15 × 10 × 10 mm was seen, larger than the usual FGP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our case was considered sporadic and probably PPI-related. A report from Japan stated that after rabeprazole was used for 104 weeks, 13.6% of patients developed new fundic gland polyps, predominantly in the gastric corpus, with sizes less than 5 mm [ 8 ]. In this index case, though there were multiple polyps in the fundus and body, a large antral polyp measuring 15 × 10 × 10 mm was seen, larger than the usual FGP.…”
Section: Discussionmentioning
confidence: 99%
“…In the current Japanese guideline, it is reported that longterm PPI therapy is generally safe; however, careful observations are required [5]. Regarding PPI-related endoscopic gastric mucosal changes, fundic gland polyps, hyperplastic polyps, multiple white and at elevated lesions, cobblestone-like mucosa, and black spots have been reported [14,15]. The safety of the long-term administration of VPZ remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known that PPIs could cause changes in the endoscopic appearance of the stomach in the form of side reactions such as fundic gland polyps, GHPs, and PHPs 3 . Regarding the endoscopic findings of PHPs, they were reported as reddish, smooth, and dome‐shaped polyps <10 mm in diameter 4 . On the contrary, some studies made reference to a case of a >20‐mm‐sized polyp in a non‐ HP infected stomach and the difficulty of diagnosing neoplasia endoscopically even when using NBI‐ME 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the endoscopic findings of PHPs, they were reported as reddish, smooth, and dome‐shaped polyps <10 mm in diameter 4 . On the contrary, some studies made reference to a case of a >20‐mm‐sized polyp in a non‐ HP infected stomach and the difficulty of diagnosing neoplasia endoscopically even when using NBI‐ME 4 . The reduction in the GHPs after the discontinuation of long‐term PPI usage is also well‐known 5 .…”
Section: Discussionmentioning
confidence: 99%